2020
DOI: 10.1073/pnas.2004356117
|View full text |Cite
|
Sign up to set email alerts
|

The influence of packing structure and interparticle forces on ultrasound transmission in granular media

Abstract: Ultrasound propagation through externally stressed, disordered granular materials was experimentally and numerically investigated. Experiments employed piezoelectric transducers to excite and detect longitudinal ultrasound waves of various frequencies traveling through randomly packed sapphire spheres subjected to uniaxial compression. The experiments featured in situ X-ray tomography and diffraction measurements of contact fabric, particle kinematics, average per-particle stress tensors, and interparticle for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 58 publications
1
15
0
Order By: Relevance
“…Despite the differences in compliance, wave speeds, and dimensionality, 2D photoelasticity studies have revealed the role of force chain statistics and fluctuations on mechanical properties [20], stick-slip [24], dynamic penetration and compaction [13,14,25], and electrical and mechanical wave transmission [6,8]. A benefit of studies employing 2D photoelastic and rubber discs is that measurements can be made over very short timescales using high-speed imaging.…”
Section: A Brief History Of Force Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the differences in compliance, wave speeds, and dimensionality, 2D photoelasticity studies have revealed the role of force chain statistics and fluctuations on mechanical properties [20], stick-slip [24], dynamic penetration and compaction [13,14,25], and electrical and mechanical wave transmission [6,8]. A benefit of studies employing 2D photoelastic and rubber discs is that measurements can be made over very short timescales using high-speed imaging.…”
Section: A Brief History Of Force Measurementsmentioning
confidence: 99%
“…Granular materials play prominent roles in landslides, avalanches, earthquakes, and river-bed mass transport, as well as in the pharmaceutical, food, and mineral processing industries [1][2][3]. The statistics, fluctuations, and organization of force chainsinter-particle forces with magnitudes greater than the average in a cohesion-less material -have been linked to: material stresses [4]; electrical and mechanical energy transport [5][6][7][8]; mechanical failure via particle fracture and inter-particle slip [9,10]; mechanical failure of confining vessels due to stress concentrations [11]; stick-slip on granular fault gouge [12]; hot spot formation during compaction of energetic powders [13]; the dynamics of intruders penetrating granular beds [14]. However, measuring time-resolved 3D force chain evolution at timescales relevant to these and other applications remains a challenge due to technological limitations and the difficulty of such experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Hertzian (or Hertz-Mindlin) contact theory underlies estimates for the nature of sound propagation in granular media (e.g., Gómez et al 2012;van den Wildenberg et al 2013) and development of a continuum model, denoted an effective medium theory (e.g., Goddard 1990;Johnson et al 2000). In granular systems, broadening and attenuation of seismic or acoustic pulses may be intrinsically related (Langlois and Jia, 2015;O'Donovan et al, 2016;Zhai et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Techniques for determining interparticle forces include those leveraging photoelastic discs [1], compliant grains imaged with X-ray tomography [2], intra-particle speckle patterns combined with digital image correlation [3], and sand grains analyzed with X-ray computed tomography (XRCT) and 3D X-ray di↵raction (3DXRD) [4]. The combination of XRCT and 3DXRD has been used in natural and synthetic particle packs to study stress distributions [5], particle fracture mechanics [6], energy dissipation [7], and wave propagation [8]. Although prior work has described sources of experimental uncertainties in stresses and inferred forces [9,10], limited work has systematically examined uncertainty propagation.…”
Section: Introductionmentioning
confidence: 99%